Identity and Academic Training of Muslim Women in the Basque Country - Ghacham-Emrani Hachmioune, Ikram (2024)
Objective.This research aimed to investigate the experiences of Muslim female students in higher education, with a focus on the categories of inclusion, intersectionality, identity, and interculturality. Method. Six Muslim women from different parts of the Basque Country were interviewed. Results. The results reveal that all participants possess a mixed identity, yet they have not seen their condition transferred to the classroom in terms of inclusion and interculturality. The results also suggest that these students have been affected by other forms of discrimination derived from their gender condition. Similarly, results indicate that they have been affected by the low expectations for academic success that teachers have projected on them across various educational stages, conditioning, to some extent, the construction of their academic biographies. Conclusions. These findings highlight the need to rethink how to build a more inclusive educational model in which interculturality is truly worked on.